A Randomized Comparison Between Conventional and Waveform-Confirmed Loss of Resistance for Thoracic Epidural Blocks. Issue 3 (1st May 2016) - Arnuntasupakul, Vanlapa; Van Zundert, Tom C.R.V.; Vijitpavan, Amorn; Aliste, Julian; Engsusophon, Phatthanaphol; Leurcharusmee, Prangmalee; Ah-Kye, Sonia; Finlayson, Roderick J.; Tran, De Q.H.
Abstract : Background and Objectives: Epidural waveform analysis (EWA) provides a simple confirmatory adjunct for loss of resistance (LOR): when the needle tip is correctly positioned inside the epidural space, pressure measurement results in a pulsatile waveform. In this randomized trial, we compared conventional and EWA-confirmed LOR in 2 teaching centers. Our research hypothesis was that EWA-confirmed LOR would decrease the failure rate of thoracic epidural blocks. Methods: One hundred patients undergoing thoracic epidural blocks for thoracic surgery, abdominal surgery, or rib fractures were randomized to conventional LOR or EWA-LOR. The operator was allowed as many attempts as necessary to achieve a satisfactory LOR (by feel) in the conventional group. In the EWA-LOR group, LOR was confirmed by connecting the epidural needle to a pressure transducer using a rigid extension tubing. Positive waveforms indicated that the needle tip was positioned inside the epidural space. The operator was allowed a maximum of 3 different intervertebral levels to obtain a positive waveform. If waveforms were still absent at the third level, the operator simply accepted LOR as the technical end point. However, the patient was retained in the EWA-LOR group (intent-to-treat analysis). After achieving a satisfactory tactile LOR (conventional group), positive waveforms (EWA-LOR group), or a third intervertebral level with LOR but no waveform (EWA-LOR group), the operator administered a 4-mL test dose of lidocaine 2% with epinephrine 5 μg/mL. Fifteen minutes after the test dose, a blinded investigator assessed the patient for sensory block to ice. Results: Compared with LOR, EWA-LOR resulted in a lower rate of primary failure (2% vs 24%; P = 0.002). Subgroup analysis based on experience level reveals that EWA-LOR outperformed conventional LOR for novice ( P = 0.001) but not expert operators. The performance time was longer in the EWA-LOR group (11.2 ± 6.2 vs 8.0 ± 4.6 minutes; P = 0.006). Both groups were comparable in terms of operator's level of expertise, depth of the epidural space, approach, and LOR medium. In the EWA-LOR group, operators obtained a pulsatile waveform with the first level attempted in 60% of patients. However, 40% of subjects required performance at a second or third level. Conclusions: Compared with its conventional counterpart, EWA-confirmed LOR results in a lower failure rate for thoracic epidural blocks (2% vs 24%) in our teaching centers. Confirmatory EWA provides significant benefits for inexperienced operators.